HUBUNGAN ANTARA SELF EFFICACY DAN KEMANDIRIAN DENGAN HASIL BELAJAR MATEMATIKA DI KELAS V SEKOLAH DASAR NEGERI 44 PONTIANAK BARAT - Chanana Chanana; Aunurrahman Aunurrahman; Tahmid Sabri (Universitas Tanjungpura, 2020)
Abstract This study aims to describe the relationship between: 1) self efficacy with learning outcomes, 2) independence with learning outcomes, 3) self efficacy, and independence joint learning outcomes, as well as 4) major responsibilities contributing to success, self efficacy and indenpendence towards the results of mathematics learning in fifth grade students of 44 Pontianak Elementary School. This study uses descriptive methods using quantytative. This type of research is correlational. This research was conducted in class V B, with a population of 65 students. Data collection is done using a questionnaire instrument. Data analysis techniques were carried out by descriptive statistical analysis, while to determine the relationship between variable variables namely self efficacy and indenpendence with mathematics learning outcomes were used through simple calculations and multiple conversions. The results showed 1) self efficacy obtained 0,550, 2) indenpendence obtained 0,456, 3) self efficacy and indenpendence in learning together with learning outcomes with the results obtained 27% of mathematics learning in fifth grade students of 44 West Pontianak Elementary School. Keywords: indenpendence, mathematics learning outcomes, self efficacy